2005
DOI: 10.1016/j.amjhyper.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal autoantibodies from preeclamptic patients activate angiotensin receptors on human mesangial cells and induce interleukin-6 and plasminogen activator inhibitor-1 secretion

Abstract: Our findings suggest that a maternal autoantibody with the ability to activate AT(1) receptors may account for the development of renal damage seen in preeclamptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 34 publications
1
52
0
3
Order By: Relevance
“…Activation of AT 1 receptors by these autoantibodies on various cell types provokes biological responses relevant to the pathophysiology of preeclampsia. [27][28][29][30][31][32] We report here that IgG from preeclamptic but not normotensive pregnant individuals stimulates sFlt-1 synthesis and secretion by pregnant mice, by human placental villous explants, and by cultured human trophoblasts. We show that these autoantibodies are capable of inducing endothelial dysfunction via sFlt-1 induction.…”
mentioning
confidence: 94%
“…Activation of AT 1 receptors by these autoantibodies on various cell types provokes biological responses relevant to the pathophysiology of preeclampsia. [27][28][29][30][31][32] We report here that IgG from preeclamptic but not normotensive pregnant individuals stimulates sFlt-1 synthesis and secretion by pregnant mice, by human placental villous explants, and by cultured human trophoblasts. We show that these autoantibodies are capable of inducing endothelial dysfunction via sFlt-1 induction.…”
mentioning
confidence: 94%
“…69 Phosphorylation of ERK1/2 (extracellular signal-regulated kinase 1/2), induction of NADPH oxidase, phosphorylation of NF-κB (nuclear factor kappa light chain enhancer of activated B cells), and promoter activation in the nucleus have been all implicated in Ang II hypersensitivity in preeclampsia. 70 Studies in rats treated with L-NAME during pregnancy suggest that hypersensitivity to Ang II may be because of oxidative stress and reduced NO bioavailability. donors in pregnant rats treated with suramin that exhibit preeclampsia-like features such as hypertension, proteinuria, and intrauterine growth restriction.…”
Section: Angiotensin IImentioning
confidence: 99%
“…PAI-1 plays a role in trophoblast invasion by inhibiting the urokinase-type plasminogen activator, resulting in decreased conversion of plasminogen to plasmin, decreased extracellular matrix digestion, and shallow trophoblast invasion. We have also shown that AT1-AA activate AT1 receptors on cultured human mesangial cells resulting in the stimulation of PAI-1 synthesis and secretion, a feature that may contribute to kidney damage leading to proteinuria, a hallmark manifestation of preeclampsia (9). Increased PAI-1 production by trophoblast cells, mesangial cells, and possibly other cell types may contribute to the hypercoagulation sometimes associated with preeclampsia.…”
Section: At1-aa May Contribute To Multiple Features Of Preeclampsiamentioning
confidence: 95%